(untitled) (Bangladesh Journal of Botany, 2022)
Conservation tillage and weed management practices were applied on maize-wheat cropping system to study the soil biological activities under Northern Himalayas region. The experiment included five tillage and three weed management treatments. Conservation agriculture (CA)-based management practices including residues incorporation (ZTR-ZTR), ZT-ZT, and ZT-ZTR showed higher soil microbial population (bacteria, fungi, and actinomycetes) and microbial activity during 2014-15 and 2015-16 in both maize and wheat crop as compared to conventional tillage (CT-CT). Among different weed management practices, IWM-IWM showed the highest microbial communities population and microbial activities as compared to the application of herbicides and weedy check. Results clearly exhibited that CA with all three proven principles (no-tillage, residue retention, and crop diversification) in the maize-wheat system along with intercrop resulted in higher microbial activities, and population compared to other conventional management systems. Bangladesh J. Bot. 51(3): 425-431, 2022 (September)